2013
DOI: 10.1371/journal.pone.0081144
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Precise Measurement of Serum Branched-Chain and Aromatic Amino Acids by Isotope Dilution Liquid Chromatography Tandem Mass Spectrometry

Abstract: BackgroundSerum branched-chain and aromatic amino acids (BCAAs and AAAs) have emerged as predictors for the future development of diabetes and may aid in diabetes risk assessment. However, the current methods for the analysis of such amino acids in biological samples are time consuming.MethodsAn isotope dilution liquid chromatography tandem mass spectrometry (ID-LC/MS/MS) method for serum BCAAs and AAAs was developed. The serum was mixed with isotope-labeled BCAA and AAA internal standards and the amino acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 24 publications
3
33
0
2
Order By: Relevance
“…Felig and colleagues [23] originally reported that BCAAs and AAAs correlated with obesity and serum insulin. More recent investigations, as well as our previous research, highlighted associations of certain amino acids with obesity, elevated serum glucose, dyslipidemia and high blood pressure [3][5], [8], [15]. The present study extends the prior work by demonstrating robust and reproducible associations of circulating levels of BCAAs and AAAs with these previously studied risk factors.…”
Section: Discussionsupporting
confidence: 87%
“…Felig and colleagues [23] originally reported that BCAAs and AAAs correlated with obesity and serum insulin. More recent investigations, as well as our previous research, highlighted associations of certain amino acids with obesity, elevated serum glucose, dyslipidemia and high blood pressure [3][5], [8], [15]. The present study extends the prior work by demonstrating robust and reproducible associations of circulating levels of BCAAs and AAAs with these previously studied risk factors.…”
Section: Discussionsupporting
confidence: 87%
“…A new longitudinal data in a population-based cohort of nondiabetic British European and South Asian men, followed up for 19 years, concluded that BCAAs and AAAs may be focuses for identifying novel etiological mechanisms and potential treatment targets for diabetes in South Asian populations as they may contribute to their excess risk of diabetes [ 26 ]. Another is that BCAAs are related to other MS components such as elevated WC, elevated TG, and decreased HDL-C in animal and clinical study [ 24 , 36 ]. A recent longitudinal study from Japan showed that plasma-free amino acids profile can predict the four-year risk for developing lifestyle-related diseases, including diabetes, dyslipidemia, and hypertension in a general Japanese population [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…High serum branched-chain amino acid (BCAA; isoleucine, leucine, and valine) concentrations have been shown to be predictors or markers of insulin resistance (1), obesity (2, 3), diabetes (4, 5), and atherogenetic dyslipidemia (6, 7) and response to a test meal (8). A 12-year prospective follow-up study of initially normoglycemic individuals showed an association between high serum BCAA levels and incidence of type 2 diabetes (4).…”
Section: Introductionmentioning
confidence: 99%